Mapping and Development Research Trends of Zakat Institutions: A Bibliometric Analysis - Zaky Mubarak Lubis; Rama Wahyudin; Gusti Dirga Alfakhri Putra; Wahyuni Lely Augusna (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
Zakat institution as a forum for the development and growth of zakat activities by carrying out various activities. The framework and patterns that are built in the development and growth of zakat institutions need attention in the form of sustainable scientific innovation. This form of effort is like providing scientific contributions through scientific research related to zakat institutions. This study aims to provide an overview and mapping of topic trends regarding zakat institution research from 2009 to 2022 through two Journal Publishing Websites, namely Google Scholar and Scopus-indexed International Journals. The results show that from Google Scholar there are 3211 topics which are then filtered to avoid Duplicate System Errors so that it becomes 944 topics of zakat institutions, then there are 200 topics from Scopus indexed journals Q1, Q2, Q3 and Q4. Each website has qualities that describe the latest topic trends of the Zakat Institute leading to future research such as discussion topics related to digitalization, management to post-covid-19 topics.